The impact of intolerance of emotional distress and uncertainty on veterans with co-occurring PTSD and substance use disorders. (June 2016) - Banducci, Anne N.; Bujarski, Sarah J.; Bonn-Miller, Marcel O.; Patel, Amee; Connolly, Kevin M.
Highlights: Veterans with co-occurring PTSD and substance use disorders are understudied. Intolerance of emotional distress is associated with PTSD symptoms among veterans. Intolerance of uncertainty interacts with intolerance of emotional distress on PTSD. Intolerance of emotional distress is associated with trauma elicited substance cravings. Abstract: The risk of developing a substance use disorder (SUD) is significantly higher among veterans with posttraumatic stress disorder (PTSD). Veterans with this co-occurrence have poorer outcomes than singly diagnosed veterans, which may be related to two risk factors: intolerance uncertainty (IU) and low tolerance of emotional distress (TED). We hypothesized low TED and high IU would independently and interactively relate to heightened PTSD symptomatology and trauma-cue elicited SUD cravings. A sample of 70 veterans ( M age = 50; 95% men; 65% Black) with co-occurring PTSD-SUD was recruited. The Posttraumatic Stress Disorder Checklist (PCL), Craving Questionnaire, Distress Tolerance Scale, and Intolerance of Uncertainty Scale were administered. In general, low TED and high IU were significantly correlated with the PCL total and subscale scores. When examined within regression models, low TED was associated with elevated PCL scores and trauma-cue elicited SUD cravings; IU was not. However, there was a significant interaction between IU and TED; veterans with elevated IU and low TED had higher PCL Total, Hyperarousal, and Intrusions scores. This highlights the importance of assessing TED and IU among veterans with co-occurring PTSD-SUD, as these risk factors may not only be prognostic indicators of outcomes, but also treatment targets.